Optimal Control of COVID-19 Model with Partial Comorbid Subpopulations and Two Isolation Treatments in Indonesia (European Journal of Pure and Applied Mathematics, 2023)
We applied sensitivity analysis and optimum control to the COVID-19 model in this research. In addition, the basic reproduction number calculated as 1.57 indicates that this illness is widespread across Indonesia. The most important factor in this model is the contact rate with infected people, with or without comorbidity. Optimal control will minimize the number of infected populations without and with comorbidity, and costs. Numerical experiments will be carried out to describe and compare the graphical models of the spread of COVID-19 with and without controls. From the numerical results and cost-effectiveness analysis on the optimal control problem, it is found that applying a combination of controls can give the best results compared to a single control
Keywords: COVID-19, sensitivity analysis, optimal control